The HIV-1 Tat Protein Stimulates Reverse Transcription In Vitro - Apolloni, Ann; Meredith, Luke W.; Suhrbier, Andreas; Kiernan, Rosemary; Harrich, David (Current HIV Research, 2007)
The role of Tat in HIV-1 reverse transcription has been controversial largely because different studies have observed disparate effects of the Tat protein on reverse transcription. Studies of HIV-1 lacking a functional tat gene demonstrated a decrease in reverse transcription efficiency following infection of T-cells however, in vitro recombinant Tat1-86 has been shown to inhibit RT activity. Here we show that 20-200 nM of both N-terminally histidine-tagged recombinant Tat1-72 and Tat1-86 stimulated reverse transcription by HIV-1 reverse transcriptase (RT) in vitro by 2-3 fold. However, both Tat species were efficient inhibitors of RT activity at 400 nM. The lower concentrations of Tat increased reverse transcription efficiency by facilitating multiple rounds of DNA synthesis, and this increase was either not seen or reduced when Tat proteins with multiply-mutated cysteine or basic domains were used. Tat-enhanced reverse transcription occurred in a RNA-independent manner, and required formation of a Tat-RT complex. Pull-down and immunoprecipitation experiments confirmed that Tat could interact with the RT p51 subunit, and mammalian two-hybrid experiments showed interaction between Tat and both the p51 and p66 subunits. Together these results provide evidence that Tat can stimulate reverse transcription through an interaction with RT.
Keywords: in vitro